Synchronous Development of Gastrointestinal Stromal Tumor and Arteriovenous Malformation in the Jejunum - Javeed, Saira Javeed; Ishaq, Ruqayya; Khalid, Ahmareen; Tanwani, Ashok Kumar (International Journal of Pathology, 2018)
This case report is about synchronous development of gastrointestinal stromal tumors (GISTs) with AVmalformations (AVMs). A 23-year-old pale woman presented with melana and anemia. Abdominal computedtomography Non Enhanced Contrast (CT-NEC) revealed a gut wall thickness in left hypochondrium andmultiple focal calcifications. Contrast enhanced computed tomography (CECT) revealed non-homogenousenhancement with circumferential gut wall thickening and narrowing lumen plus AV malformations in thegut wall giving impression of mass in the jejunum with AV malformation. An exploratory laprotomy wasperformed. The resected jejunum showed a protruding solid mass. The mass was confirmed to be a spindlecell type GIST and was intermingled with the AVM. To our knowledge, this is the second case of an AVMassociated with a GIST. First case was reported in 2008 by Shim SH et al 1.